Henryk Sienkiewicz’s Works as a Factor in the Struggle for the Revival of the Polish State: According to the materials of the Department of Library Collections and Historical Collections of V. I. Vernadskyi National Library of Ukraine - Ivanna Gurzhiy (Київські історичні студії)
Having lost statehood at the end of the 18th century, the people of the Polish-Lithuanian Commonwealth desperately tried to regain it, organizing the November Uprising in 1830, and later the January Uprising in 1863–1864. Given the fact that historical science in the 19th century was elitist in nature, there was an urgent need to convey free-thinking national ideas and thoughts to the average citizen, in connection with which scientists very often resorted to journalism and literary creativity. It should be noted that for ordinary people deprived of independence, literature turned into a kind of “moral core” and a criterion of patriotism. The study deals with the publications of Henryk Sienkevych from the foreign literature fund, the Department of Library Collections and Historical Collections of V. I. Vernadskyi National Library of Ukraine with signs of their belonging to private book collections of representatives of the intelligentsia of the second half of the 19th — early 20th centuries. The scientific novelty lies in identifying the connections of Henryk Sienkiewicz with other personalities of the literary, scientific and publishing world. As a result of the scientific search and review of publications, some of the books from the book collections of the Polish and Ukrainian music publisher Leon Idzikowsky, the Polish politician Jan Wysniewski, the Warsaw agronomist Kazimierz Mostowski, the historian and ethnographer Mytrofan Dovnar-Zapolsky and others were found. The emergence in the second half of the 19th century of such an extraordinary figure as Henryk Sienkiewicz was largely due to new socio-political phenomena of a conceptual nature, which was particularly clearly affected by the national desire for Poland to regain independence from the Russian Empire. The writer’s efforts to pay as much attention as possible to the struggle of the Poles for national freedom often led to the fact that in his works of art the anti-Ukrainian ideological orientation became one of the dominant ones, a manifestation of the subjective perception of historical events. At the same time, the activity of the Polish artist, communication with extraordinary people in his country (M. Konopnytska, B. Prus, G. Siemiradsky) and beyond its borders, immersion in the national and world past inspired more than one generation of fellow citizens to resist the oppression of the tsarist government. This is clearly evidenced by the materials of the fund of the Department of Library Collections and Historical Collections of the V. I. Vernadskyi National Library of Ukraine.